Repertoire of food acquisition behaviors in Western Palearctic shorebirds (Aves, Charadriiformes) - Baguette, Michel; Le Floch, Glenn; Hannier, Lyse; Kirchhoff, Florence; Schtickzelle, Nicolas; Stevens, Virginie M.; Bels, Vincent (Frontiers in Ethology, 2024)
Shorebirds are iconic examples of food resource partitioning through use of contrasted morphological structures to acquire food. Differences in beak lengths and shapes allow species catching their food at various sediment depths. Contrasted leg lengths allow species foraging at distinct water depths. Despite these morphological differences, shorebirds use a small number of stereotyped behaviors for food acquisition. We classify these behaviors by analyzing video sequences of ca. two dozen species of Western Palearctic shorebirds, during migration or wintering. We suggest disassembling food acquisition in three successive stages: foraging, feeding, and swallowing. The foraging stage regroups the locomotion behaviors associated to food detection, and the behaviors used during food capture. The feeding stage encompasses the handling behaviors used to kill or stun the prey and to extract its edible parts, and the behaviors used to transport the prey from the distal part of the beak to the bird's pharynx. In the swallowing stage, the edible parts of the prey enter the pharynx. We show that three of these behaviors (locomotion, capture and transport) are made up of stereotypical, mutually exclusive components, and can be considered as performances. Each of our study species use one or maximum two components of these three performances. Overall, our study provides insights on interspecific variation in shorebird food acquisition behaviors that we put in a phylogenetic perspective. We confirm the long-standing hypothesis that pecking is the plesiomorphic behavior of food capture, and we show that those locomotion and transport behaviors associated with pecking differ from those associated with derived capture behaviors, leading to a syndrome of food acquisition behaviors in shorebirds. a supprimé: improve the 128 a mis en forme : Normal a supprimé: o 129 a supprimé: recorded 130 a mis en forme : Police :Non Italique a supprimé: respectively 131 a supprimé: . ¶